Comparison of efficacy of phased multipolar versus traditional radiofrequency ablation: A prospective, multicenter study (CAPCOST). Issue 7 (14th June 2019) - Essebag, Vidal; Azizi, Zahra; Alipour, Pouria; Khaykin, Yaariv; Leong‐Sit, Peter; Sarrazin, Jean‐Francois; Sturmer, Marcio; Morillo, Carlos; Terricabras, Maria; Amit, Guy; Roux, Jean‐Francois; Patterson, Sherri; et al.
Abstract: Background: Multipolar phased pulmonary vein ablation catheter (PVAC), specifically its second‐generation (PVAC‐Gold), has been associated with reduced procedural time for atrial fibrillation (AF) ablation compared to traditional catheters. We performed this study to compare the efficacy of PVAC with point‐by‐point radiofrequency (RF) ablation. Methods: This is a multicenter‐cohort study (2012‐2017), involving patients with symptomatic, paroxysmal AF refractory to at least one antiarrhythmic medication. Overall, 230 patients were enrolled to (A) PVAC and (B) control groups. Subanalyses were done for ablations performed with PVAC‐Gold, and for ablations performed without left atrial (LA) ablation in addition to pulmonary vein isolation. Electrocardiogram and 48‐h Holter monitoring were used to assess patients at 3, 6, 9, and 12 months postablation. Recurrence was defined as any atrial arrhythmia >30 s excluding an initial 3‐month blanking period. Results: Freedom from any atrial arrhythmia at 12 months postablation was 35.70% and 52.80% in groups A and B, respectively ( P  = .01). Freedom from atrial arrhythmia was not significantly different when limiting the PVAC cohort to PVAC‐Gold and excluding patients with additional LA ablation (A: 44.30%; B: 44.30%, P  = .80). Procedural and ablation time was significantly lower in group A than B. Multivariate regression model showed female gender (odds ratio [OR] = 2.90) and recurrence during blanking period (OR = 6.60) as significant predictors of recurrence. Conclusion: This study suggests that PVAC may achieve less freedom from AF than point‐by‐point RF; however, efficacy is similar when comparing PVAC‐Gold and point‐by‐point stand‐alone PV isolation. PVAC is associated with significantly reduced procedural times for AF ablation.